Weak of Effects of Music Education in The Establishment of Characters - Wicaksono, Herwin Yogo (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2019)
This study discusses the absence of significant influence from music education in shaping an individual’s character. Character education itself is an education that discusses the mental and moral qualities that are unique to an individual. Ki Hajar Dewantara views music education as having the power to help Indonesian people realize a better inner and outer life, and the nature of the art of music itself is actually order and beauty. The purpose of this study is to reveal the weak influence of music education on the formation of an individual’s character. The behaviour of students and lecturers in the Department of Music Education FBS UNY was observed continuously for approximately six months. To strengthen the data, interviews were conducted face to face. The results showed that most students and lecturers who had long struggled and involved in the music field were weak in terms of discipline, social care and socializing order, and beauty. This can be seen from the behaviour of students and lecturers in carrying out daily activities, especially musical activities.